2022
DOI: 10.2967/jnumed.122.264080
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Silicon Photomultiplier Time-of-Flight Dedicated Head PET System for Clinical Brain Studies

Abstract: We acquired brain positron emission tomography (PET) images of fluorodeoxyglucose (FDG) and flutemetamol PET using a time-of-flight-PET system dedicated for the head (dhPET) and a conventional whole-body PET/computed tomography (wbPET) system and evaluated the clinical superiority of dhPET over wbPET. Methods: There were 18 subjects for the FDG-PET study and 17 subjects for the flutemetamol PET study. FDG-PET images were first obtained using wbPET, followed by dhPET. Flutemetamol PET images were first obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…It has been considered that conventional WB PET scanners are inadequate to evaluate small brain structures, including brainstem nuclei, because of their relatively poor spatial resolution. Indeed, several reports have described PET-tracer uptake in the brainstem nuclei using head-dedicated PET scanners [ 12 , 13 , 16 ]. For example, Takahashi et al described that FDG uptake in small brainstem nuclei such as the IC, RN, and MRN were more clearly detected by a brain-dedicated PET system with a hemispherical shape than by WB PET [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been considered that conventional WB PET scanners are inadequate to evaluate small brain structures, including brainstem nuclei, because of their relatively poor spatial resolution. Indeed, several reports have described PET-tracer uptake in the brainstem nuclei using head-dedicated PET scanners [ 12 , 13 , 16 ]. For example, Takahashi et al described that FDG uptake in small brainstem nuclei such as the IC, RN, and MRN were more clearly detected by a brain-dedicated PET system with a hemispherical shape than by WB PET [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can be a proof of better imaging performance of VRAIN than HRRT. For the comparison with BresTome, of which crystal size is 2.1 mm×15 mm long, another clinical image of VRAIN (Iwao et al 2022) can be compared with clinical images in Ishii et al (2022), and the comparison is shown in Supplemental figure 3. The similar slices which can be easily compared with Ishii et al (2022) are shown.…”
Section: Discussionmentioning
confidence: 99%
“…For the comparison with BresTome, of which crystal size is 2.1 mm×15 mm long, another clinical image of VRAIN (Iwao et al 2022) can be compared with clinical images in Ishii et al (2022), and the comparison is shown in Supplemental figure 3. The similar slices which can be easily compared with Ishii et al (2022) are shown. Acquisition time of 30 min and injected activity at the start time of acqusition (123 MBq) are the same, while post-injection time is different (107 min in VRAIN and 71±5 min in BresTome) and the subject in BresTome was a 85 years old male patient with mild cognitive impairment due to AD (22 years old healthy male volunteer in VRAIN).…”
Section: Discussionmentioning
confidence: 99%
“…This means that one scanner can be used for both dhPET and dbPET. Recent studies have evaluated the image quality provided by this scanner as a dhPET system [ 9 , 10 , 11 ], but regarding its image quality as a dbPET system, we have found no reports of a comparison between this scanner and its prior model, the PMT-based dbPET scanner. We conducted the present phantom study to qualitatively and quantitatively compare the image quality of organ-specific SiPM-based TOF-PET and PMT-based PET for breast imaging.…”
Section: Introductionmentioning
confidence: 99%